2022
DOI: 10.1037/ccp0000667
|View full text |Cite
|
Sign up to set email alerts
|

Therapist adaptations to evidence-based practices and associations with implementation outcomes in child therapy sessions.

Abstract: Objective: Community therapists inevitably adapt evidence-based practices (EBPs) to meet the needs of their clients and practice settings. Yet, the implications of spontaneous, therapist-driven adaptations for EBP implementation outcomes are not well understood. We used a sequential QUAN → qual mixed-methods design to examine how different types of therapist-described adaptations were associated with observerrated extensiveness of therapist delivery of EBP content and technique strategies at the session level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Integrating theory-driven and data-driven approaches in their study, Yu et al (2021) used mixed-method analyses. Specifically, quantitative analyses (multilevel regression models) were conducted to test whether therapists adapted the treatments they provided, and qualitative analyses (grounded theory) were used to explore how and why therapists adapted their treatments.…”
Section: What Is the Tailoring Approach?mentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating theory-driven and data-driven approaches in their study, Yu et al (2021) used mixed-method analyses. Specifically, quantitative analyses (multilevel regression models) were conducted to test whether therapists adapted the treatments they provided, and qualitative analyses (grounded theory) were used to explore how and why therapists adapted their treatments.…”
Section: What Is the Tailoring Approach?mentioning
confidence: 99%
“…Thus, this study demonstrates an integration of controlled and naturalistic methods. Another good example comes from the study by Yu et al (2021) in which the authors were interested in testing therapists' spontaneous adaptation of treatments to local contexts. They were interested in investigating the ways in which community therapists, who hold valuable expertise about the communities they serve, adapt treatment implementation to their patients' unique characteristics and needs.…”
Section: Which Research Designs Should Be Used?mentioning
confidence: 99%
“…Further, although most EBPs were developed and studied in academic settings, research suggests that their dissemination in community settings requires guidance on how to maintain the course when clients struggle with EBP content [ 10 , 11 ]. When clients do not respond to treatment, therapists may need support to lean into flexible, innovative ways of delivering, teaching, or presenting EBPs to promote engagement, understanding, and fit of therapy [ 12 ]. This reality makes it an opportune time to introduce digital tools like artificial intelligence (AI) platforms that can support therapists as they provide EBPs and seek to reduce workload [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study involving observation-based coding of modifications over the full treatment protocol, Marques et al found that in a sample of Spanish- and English-speaking consumers in a community mental health setting, both fidelity and modifications that remained consistent with the CPT protocol were associated with increased treatment effectiveness ( 9 ). In another study, Yu et al found that two therapist-described adaptations (extending of the protocol and modification of content) were associated with the extensiveness with which protocol elements were covered in youth mental health settings ( 10 ). High quality documentation is necessary to advance efforts to understand the types of modifications that are made and the impact that they have on both clinical and implementation outcomes ( 1 ).…”
Section: Introductionmentioning
confidence: 99%